P173 Plasma and tumour tissue TP53-gene expression in patients with high grade serous advanced ovarian cancer. (1st November 2019) - Martinez-Garcia, J; Sanchez Henarejos, P; Jimenez Lucas, MD; Puertes Boix, A; Anton Garcia, A; Perez Sanz, F; Rodriguez Braun, E; Cano Jimenez, A; Collado Martinez, D; Lopez Muñoz, A; Quiros Figallo, T; Sanchez, D; et al.
Abstract : Introduction/Background: TP53 is a tumour suppressor gene frequently mutated in high grade serous ovarian cancer(HGSOC).The aim of this study is to investigate the expression of TP5-gene in cell-free DNA(cfDNA) in plasma and tumour paraffin-embedded tissue in HGSOC, both platinum-sensitive(PSR)and platinum-resistant relapse(PRR)patients. Methodology: This multicentric prospective observational study has been conducted from November/2013 to February/2017 in patients diagnosed of HGSOC.Ampliseq custom panel was designed to amplify TP53-gene.Libraries passing QC were sequenced on the PGM Ion Torrent using a Hi-Q view sequencing kit and 318 chip v.2. The sequence data generated were mapped with the Torrent Suite 5.8.This study was approved by the Central Research Ethics Committee. Results: We analyzed plasma and tumour samples of 30 patients(16 PSR and 14 PRR).The most frequently detected mutations were missense mutations.Mutations in circulating TP53 were found in tumour tissue in only 24% of patients and mutations in tumour tissue were found in circulating TP53 in only 12%.There was no difference in TP53 gene expression in PSR and PRR patients nor with other clinical variables, neither with circulating DNA nor tumour paraffin-embedded tissue.In 4 tumour tissue were not detected any mutations(13% patients;2 PSR, 2 PRR).In 3 circulating TP53 were not any mutations (10% patients;1PSR, 2 PRR).We also analysed 5 healthy controls whose we were not detected any mutations in TP53 in plasma.The number of TP53 mutations have not related to the tumour response.The number of TP53 mutations in tumour tissue was related with progression-free survival (p 0, 001) and overall survival (p<0, 001), but not with mutations in circulating TP53. Conclusion: The number of TP53 mutations in tumour tissue have been prognostic factor for progression-free and overall survival in HGSOC.Most of HGSOC had mutation of circulating TP53, both in circulating DNA and tumour paraffin-embedded tissue.We have not found significant difference in the expression of TP53-gene in platinum-sensitive and platinum-resistant HGSOC nor with other clinical variables. Disclosure: Nothing to disclose.